Physical Resource Management for Senior Secondary School Effectiveness in Biu Education Zone of Borno State, Nigeria - Saidu, Abdulkadir Mohammed; Machar, Samuel; Mallum, Musa (International Journal of Educational Management, 2021)
This study determines thePhysical Resource Management for Senior Secondary School Effectiveness in Biu Education Zone of Borno State, Nigeria. Correlation and survey research design were used for this study. Three objectives, two research questions and one hypothesis were used in the study. Correlation research design was used to determine the relationship between physical resources management and school effectiveness while survey was used to ascertain the availability in senior secondary school in Biu education zone. Correlation design according to Cohen andManion, (2009) aimed at determining the nature, degree and direction of relationship between variables or using these relationships to make predictions. The population of this study comprised eighteen (18) senior secondary schools in Biu Education zone with 2781 as population. Simple random sampling was used in drawing the sample of ten (10) senior secondary schools and 326 teachers. Simple random sampling according to Johnson and Christensen (2008) is a sample drawn by a procedure which every member of the population has an equal chance to be represented in the study. Self-developed Checklist titled: Physical Resource Management (PRM) was used as instrument for data collection. The Checklist consisted of four (10) items which sought information on the Availability and utilization of physical resource where the respondents ticked the options which were scored as follows: Adequately Available (AA); Available (A); Moderately Available (MA); Not Available (NA). However, in determining the validity and reliability of the instrument, experts in Educational Measurement and Evaluation, Department of Education, Faculty of Education- University of Maiduguri validated the instruments. Cronbach’s Alpha was adopted to measure the reliability of the instrument which stood at 0.93.The data was analyzed using simple percentage and Pearson Product moment correlation coefficient.Based on the above findings the researchers conclude that physical resources are the major predictor of senior secondary school effectiveness. This implies that physical resources play a significant roles in determined the senior secondary school effectiveness. The researchers also recommended that Non-Governmental organization should complement the efforts of State Government in the provision of physical resources in senior secondary school as it found to influences it effectiveness in Biu Education Zone, Borno State.